Compatibility of a predator and an entomopathogenic fungus of Asian citrus psyllid - Beghelli, Gabriel Modesto (2024)
The Asian citrus psyllid Diaphorina citri Kuwayama (Hempitera: Pysllidae) is a major pest of citrus because it vectors bacteria associated with Huanglongbing, the most destructive citrus disease. This disease causes severe economic losses in citrus production worldwide. Attempts to prevent disease dissemination have mainly focused on use of pesticides to control the vector, but this did not prevent disease spread. Besides, the intensive use of pesticides reduces densities of natural enemies and favors the development of resistance in the psyllids, resulting in pest resurgence. Thus, other strategies are needed for control of D. citri and Huanglongbing. One promising method is biological control; several natural enemies of psyllids in citrus orchards have been identified, but of those, only entomopathogenic fungi are commercially available, for instance Cordyceps fumosorosea (Wize, 1904) (Hypocreales: Cordycipitaceae). Generalist predators show great potential in preventing psyllid invasions and reducing disease spread because they can be released preventively with the addition of alternative food. The predatory mite Amblyseius herbicolus (Chant, 1959) (Acari: Phytoseiidae) is such a generalist and showed promise in controlling D. citri. However, little is known about its compatibility with the entomopathogen. Recent studies have shown that predatory mites can vector fungal spores to pests. Hence, the concurrent use of predators and entomopathogens may enhance control of D. citri. However, those agents could also affect each other’s actions negatively: entomopathogenic fungi can potentially infect predatory mites. Therefore, I studied the pathogenicity of C. fumosorosea for A. herbicolus. I found that the fungus had no detrimental effect on survival, development and reproduction of the predator, suggesting that both agents can be used together for the control of the psyllid. I also aimed to assess the effects of concurrent use of predator and pathogen on the population dynamics of D. citri. The combination of both agents did not reduce psyllid densities on plants better than the pathogen alone. However, the predators went extinct on all plants during the experiment, and its reason remains to be investigated. In conclusion, life history traits of A. herbicolus are not influenced by direct exposure to C. fumosorosea but it is unclear if the simultaneous use of both agents would be beneficial for biocontrol of Asian citrus psyllid. Keywords: Citrus greening. Biological control. Generalist predator. Hypocrealean fungus.